“Reading the Fruits on the Tree of Life Planted in the Paradise of Holy Scripture.” The Use and Production of Sermons in Female Communities in the Low Countries - Stoop, Patricia (Women Read. Differently? Text in Women Convents from the 13th to the 15th Centuries, 2026)

De boeken van Catherine Wouters: wat een Brusselse zuster ons leert over de middeleeuwse en vroegmoderne religieuze leescultuu - Stoop, Patricia (De Boekenwereld, 2025)

Unveiling Voices: Collective and Layered Authorship in the Sermon Collection of Maria van Pee - Stoop, Patricia (Medieval Sermon Studies, 2025)

Books for Eternity - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Collatio and Codex in the Context of the Devotio Moderna - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Consolation in Late Medieval Dutch Literature - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Die gheestelicke melody. A Program for the Spiritual Life in a Middle Dutch Song Cycle - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)
Heruitgave van: Mertens, T. (2009). Die Cheestelicke Melody: A Program for the Spiritual Life in a Middle Dutch Song Cycle. In A. B. Mulder-Bakker & McAvoy, L. H. (Red.), Women and experience in later medieval writing: reading the book of life (pp. 123-148). New York: Palgrave MacMillan.

Ghostwriting Sisters. The Preservation of Dutch Sermons of Father Confessors in the Fifteenth and the Early Sixteenth Century - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)
Heruitgave van: Mertens, T. (2004). Ghostwriting sisters: The preservation of Dutch sermons of father confessors in the fifteenth and the early sixteenth century. In A. B. Mulder-Bakker (Red.), Seeing and Knowing. Women and Learning in Medieval Europe, 1200-1550 (Vol. 11, pp. 121-141). Turnhout: Brepols.

Hendrik Mande’s Apocalypse - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

The Middle Dutch Sermon. A Premature Synthesis - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

The Monastery as a Literary Institution in the Low Countries (13th–16th Century) - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Mystical Culture and Literature in the Late Middle Ages - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Private Revelation and Public Relevance in the Middle Dutch Sermon Cycle Jhesus collacien - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Reading with a Pen. Developments in Late Medieval Spiritual Prose - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

The Sermons of Johannes Brugman OFM († 1473). Preservation and Form - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)
Heruitgave van: Mertens, T. (2007). The sermons of Johannes Brugman, OFM († 1473): preservation and form. In R. Anderson (Red.), Constructing Medieval Sermon (Vol. 6, pp. 253-274). Turnhout: Brepols.

Spiritual Testaments in the Late Medieval Low Countries. An Exploration of the Genre - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Voices without Words. Hendrik Mande’s Spiritual ‘Love Complaint’ as a Mystical Dialogue - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Diverging Perceptions: Johannes Tauler in Sixteenth-Century Printed Editions - Schepers, Kees (Circulating the Word of God in Medieval and Early Modern Europe. Catholic Preaching and Preachers across Manuscript and Print (c. 1450 to c. 1550), 2023)

The Gouda Gospel Sermons: The Glosses of a Successful Middle Dutch Pericope Collection (1477-1553) - Mertens, Thom (Circulating the Word of God in Medieval and Early Modern Europe. Catholic Preaching and Preachers across Manuscript and Print (c. 1450 to c. 1550), 2023)

Preaching the Observant Reform in Female Communities Related to the Devotio moderna - Stoop, Patricia (Observant Reforms and Cultural Production in Europe. Learning, Liturgy and Spiritual Practice, 2023)

Strategies of Publishing: The Case of Franciscus Costerus - Stoop, Patricia (Circulating the Word of God in Medieval and Early Modern Europe. Catholic Preaching and Preachers across Manuscript and Print (c. 1450 to c. 1550), 2023)

Bridging the Convent Wall. Female Book Producers in the Convent of Jericho and Collaboration with Male Intermediaries - Stoop, Patricia (Queeste, 2022)

Incunabula in Communities of Canonesses Regular and Tertiaries Related to the Devotio Moderna. Toward an ‘Inclusive’ Approach of Late Medieval Book Ownership in the Low Countries - Dlabačová, Anna; Stoop, Patricia (Quaerendo, 2021)

Johannes Mahusius’ preek op het Onze Vader als gedragsregel voor de cisterciënzinnen van Ter Kameren - Stoop, Patricia; Mariën, Emily (Ons Geestelijk Erf, 2021)

Het Brusselse Jerichoklooster - Stoop, Patricia (De Moderne Devotie. Spiritualiteit en cultuur vanaf de late Middeleeuwen, 2018)

From Reading to Writing: The Multiple Levels of Literacy of the Sister Scribes in the Brussels Convent of Jericho - Stoop, Patricia (Nuns’ Literacies in Medieval Europe. The Kansas City Dialogue, 2015)

Memory and Reward. Dutch Collections of Sermons and their Functions in the Memoria Tradition in the Female Convent of Jericho in Brussels (c. 1450-1650) - Stoop, Patricia; Mertens, Thom (The Medieval Low Countries, 2015)

Vijf preken uit de kerstkring van 1574 van Henricus Cool, vicaris van het kartuizerinnenklooster Sint-Anna-ter-Woestijne bij Brugge (Brussel, Koninklijke Bibliotheek, II 2098) - Vroomen, Lisanne; Stoop, Patricia (Ons Geestelijk Erf, 2015)

A Web of Texts: Sixteenth-Century Mystical Culture and the Arnhem Saint-Agnes Convent - Schepers, Kees (Nuns’ Literacies in Medieval Europe. The Kansas City Dialogue, 2015)

Nuns’ Literacy in Sixteenth‑Century Convent Sermons from the Cistercian Abbey of Ter Kameren - Stoop, Patricia (Nuns’ Literacies in Medieval Europe: The Hull Dialogue, 2013)

Praying in the Vernacular: Middle Dutch Imitative Forms of the Divine Office from the 1370s to 1520s - Mertens, Thom (Nuns’ Literacies in Medieval Europe: The Hull Dialogue, 2013)

Schrijven in commissie. De zusters uit het Brusselse klooster Jericho en de preken van hun biechtvaders (ca. 1456-1510) - Stoop, Patricia (Middeleeuwse studies en bronnen, 2013)

Writing, Editing, and Rearranging: Griet Essinchghes and her Version of the Sister-Book of Diepenveen - Scheepsma, Wybren F. (Nuns’ Literacies in Medieval Europe: The Hull Dialogue, 2013)

Dits scrifte dat nu in der handen es. Writing for Third Parties in the Brussels Convent of Jericho - Stoop, Patricia (Quaerendo, 2012)

Sermon-Writing Women: Fifteenth-Century Vernacular Sermons from the Augustinian Convent of Jericho in Brussels - Stoop, Patricia (The Journal of Medieval Religious Cultures, 2012)

Schrijven pro pretio in Jericho - Stoop, Patricia (De letter levend maken. Opstellen aangeboden aan Guido de Baere bij zijn zeventigste verjaardag, 2010)

De bijbelvertaling in Middelnederlandse epistel- en evangeliepreken: "Wat wi verstaen bi deser" - Stoop, Patricia (Middelnederlandse bijbelvertalingen, 2007)

The writing sisters of Jericho: authors or copyists? - Stoop, Patricia (Constructing Medieval Sermon, 2007)

Den rechten wech te hemelrijke waert. Een Middelnederlandse berijmde bewerking van De tribus dietis van Robert de Sorbon - Mertens, Thom (Op reis met Memoria, 2004)

Levende beelden? Pelgrims op de planken’ - Stoop, Patricia (Op reis met Memoria, 2004)

Middelnederlandse pelgrimages, hoever en waarheen? Een verkenning - Biesheuvel, Ingrid (Op reis met Memoria, 2004)

Pelgrims naar het land van de minne: Mystagogie en memoria bij Hadewijch van Brabant - Willaert, Frank (Op reis met Memoria, 2004)

Repertorium of Middle Dutch Sermons: Introduction - Sherwood-Smith, Maria; Stoop, Patricia (Medieval Sermon Studies, 2003)